GAMBARAN HYGIENE SANITASI PENGOLAHAN ES BATU KRISTAL DI CV KIC KABUPATEN KEBUMEN TAHUN 2023 - Afifatul Inayah Arrosidah Inayah Arrosidah; Joko Malis Sunarno; Dwi Atin Faidah (Unit Penelitian dan Pengabdian Masyarakat, Politeknik Banjarnegara, 2023)
Crystal ice cubes are a food product that is very well known by the public. As a mixture of ice cubes, there is a risk of becoming a disease-transmitting agent. Bacterial contamination factors in ice cubes include the processing process. CV KIC is one of the crystal ice cube producers in Kebumen Regency. This study aims to describe the sanitary hygiene of crystal ice processing and the coliform content in crystal ice at CV KIC, Kebumen Regency. This type of research is descriptive research with a cross-sectional approach. The research was carried out from April to June 2023. The number of samples for this study was two samples of raw material water (A) and water after going through the processing stage (B) and employees at CV KIC. The method used in this examination is the Most Probable Number (MPN). The research data were analyzed univariately. The results showed that the content of coliform bacteria showed that sample A was classified as fulfilling the requirements and sample B was classified as not fulfilling the requirements of Permenkes No. 2 of 2023. The results of sanitary hygiene inspections for crystal ice processing showed that handler hygiene was 60%, equipment sanitation was 100% and site sanitation was 77.7%. Manufacturers of crystal ice cubes should pay more attention to the cleanliness of the handlers and the equipment used to process crystal ice cubes